Study of Cellulose Extraction from Robusta Coffee Husk Using NaOH Solution - Daniati, Rahma; Zulnazri, Zulnazri; Hakim, Lukman; Hasbullah, Siti Aishah (Malikussaleh University, Aceh, Indonesia, 2022)
This study reports on manufacturing cellulose from robusta coffee husks through a solid-liquid extraction process. A high yield of cellulose can be achieved by extraction using 3.5% HNO3 at a temperature of 100 oC with a gain of 35.4%. Meanwhile, the extraction process with 4.5% HNO3 at a temperature of 80 oC only achieved a yield of 32.8%. From the results of this study, it can be seen that the smaller the concentration of HNO3 used and the higher the temperature, the greater the yield of cellulose produced. The X-ray diffraction pattern shows high peaks appearing at an angle of 2Î¸ around 22.5o; this area is a typical peak of the cellulose structure. High crystallinity was obtained at a concentration of 3.5% HNO3 at a temperature of 100 oC at 82.47%, while the lowest crystallinity was found at a 5.5% HNO3 concentration at a temperature of 100 oC at 74.27%. The decrease in crystallinity was caused by the high temperature and concentration of HNO3, which caused the acid to penetrate quickly into the cellulose tissue layer and hydrolyze the crystalline regions of cellulose. FT-IR analysis showed a high absorption area at 3314 cm-1 and a low absorption area at 1028 cm-1, typical of Robusta coffee husk cellulose. The absorption located around the 3314 cm-1 bands is a stretch of the â€“OH group and the absorption in the 1028 cm-1 band is related to the -CH2 group. SEM can show the morphology of cellulose with smaller and uniform crystal dimensions with a scale of 20 Âµm.